DISCOURSE-BASED SYLLABUS FOR TEACHING LITERATURE TO EFL LEARNERS IN VIETNAM - Lien, Tran Thi Ngoc (Indonesian Journal of Applied Linguistics, 2014)
Abstract: This paper focuses on the potential use of discourse analysis in literature teaching in EFL class as well as approaches to designing discourse-based syllabus. This non-conventional approach has radically changed the teaching culture at Haiphong Private University, Vietnam which used to consider the analysis of literary works as reading comprehension lesson. Using this novel syllabus has gradually formed a so-called 3D(imention) class in which the teacher talks, the students talk and the literary text talk from its properties and as a result the ultimate objectives of literature teaching, say, language competence and literary appreciation can be achieved. Also, some parts of the sample syllabus are shared with a hope that they will be of certain benefit to readers. Key words: syllabus, literature teaching, discourse, discourse analysis SILABUS BERBASIS WACANA UNTUK MENGAJAR SASTRA PADA PEMBELAJAR BAHASA INGGRIS SEBAGAI BAHASA ASING DI VIETNAM  Abstrak: Makalah ini focus pada penggunaan analisis wacana yang potensial pada pengajaran sastra di kelas bahasa Inggris sebagai bahasa Asing (EFL) dan juga pendekatan-pendekatan untuk merancang silabus berbasis wacana. Pendekatan yang tidak biasa ini telah benar-benar mengubah budaya mengajar di Haiphong Private University, Vietnam, yang sebelumnya biasa menganggap analisis karya sastra sebagai pelajaran membaca. Penggunaan silabus baru ini telah secara bertahap membentuk apa yang disebut kelas 3D(imention), dimana guru berbicara, mahasiswa berbicara dan karya sastra berbicara dari sifat-sifatnya, sehingga tujuan-tujuan utama pengajaran sastra, misalnya kompetensi bahasa dan penghargaan terhadap sastra bias dicapai. Selain itu, beberapa bagian dari contoh silabus tersebut dibagikan dengan harapan bisa bermanfaat bagi para pembaca. Kata kunci: Silabus, pengajaran sastra, wacana, analisis wacana